The Other Side of Sexting: Relationship between Perspective and Victimization - Ergüll, Dila; Ziyalar, Neylan (The Bulletin of Legal Medicine, 2022)
Objective: Sexting is emerged as a result of the frequent use of internet and social media to send messages, photos and videos quickly and easily and it became a common concept nowadays. In this sense, the aim of the study is to determine the factors which affects the perspective towards sexting and to investigate whether there is a relationship between victimization and sexting. Methods: The sample of this research is consisted of 565 participants who are ≥18 years. Theory of Reasoned Action has been used as a background theory to predict and determine the perspective towards sexting and sexting behaviour. The data were collected by using demographic information form and sexting scale which are prepared by researchers. Results: It was determined that a great majority of the participants engaged in sexting, men had more positive attitude and more frequent behaviour compared to women, and being a victim of sexting did not make a significant difference on the perspective towards sexting. The proportion of individuals who became a victim because of sexting is 22.5% and most of them were women. According to types of victimization, individuals mostly experience emotional and psychological problems; however, it has been determined that the victimization is not limited to a single form. Conclusion: The prevalence of sexting, perspectives of the individuals and their motivation to act are determined to a certain extent. In this way, the case of unconsidered sexting in Türkiye is identified and it is asserted that it can cause serious problems worth considering.